Impact of pavement on increasing social interactions in urban spaces of Bojnourd (Case study: Taleghani Street, Shahid Square to Telecommunication Area) - arash sadri; arezu bankian tabrizi; shadi refaei afsharghezelbash (تحقیقات کاربردی علوم جغرافیایی)
This article was written with the aim of the pedestrian impact on increasing social interactions in urban spaces of Bojnourd, with emphasis on social dimensions of social interaction. The method of this research is descriptive-analytic, which first of all has been designed to identify theoretical perspectives, general criteria of environmental quality and then collect field data and interviews with residents. Data analysis was performed using SWOT method. Case study is Taleghani street of Bojnourd. The results showed that the effect of physical properties on the quality of urban environments is in the first priority. Then, perception of the environment in the second priority and functional characteristics are in the top priority. According to the results, the most important independent variables in these three categories (physical, cultural and environmental) (security priorities, accessibility, passages, economic functions, urban environment, quality of social environment, social interactions Cultural activities, urban amenities, and recreational and lighting functions have the least impact.